2021
DOI: 10.3390/cancers13081750
|View full text |Cite
|
Sign up to set email alerts
|

Combined Assessment of Immune Checkpoint Regulator VISTA on Tumor-Associated Immune Cells and Platelet-to-Lymphocyte Ratio Identifies Advanced Germ Cell Tumors with Higher Risk of Unfavorable Outcomes

Abstract: In the current study, we aimed to investigate whether expression of immune checkpoint proteins (V-domain Ig suppressor of T cell activation (VISTA) and programmed death-ligand 1 (PD-L1)) and markers of systemic inflammation could predict progression/relapse and death in the cohort of 180 patients with testicular germ-cell tumors (GCTs). Expression of PD-L1 and VISTA was assessed by immunohistochemistry utilizing tissue microarrays. To estimate systemic inflammation neutrophil-to-lymphocyte ratio (NLR), lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
3
12
0
Order By: Relevance
“…Local tumor microenvironment and systemic immune or inflammatory response seem to influence each other in cancer patients [ 38 ]. Xiang et al demonstrated that high NLR was associated with worse OS and decreased CD8 + /CD28 − and CD4 + /CD25 + cell subsets in pancreatic cancer settings [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local tumor microenvironment and systemic immune or inflammatory response seem to influence each other in cancer patients [ 38 ]. Xiang et al demonstrated that high NLR was associated with worse OS and decreased CD8 + /CD28 − and CD4 + /CD25 + cell subsets in pancreatic cancer settings [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is implicated in several aspects of cancer biology, including cancer development, progression and prognosis [ 5 , 35 , 36 ]. The malignant process influences the host immune system not only at the tumor site but also on a global level by forming a systemic inflammatory response [ 37 ]. An impaired intratumoral inflammatory response and an elevated systemic response suggests decreased immunological control of tumors at the local level, whereas the formation of a systemic pro-inflammatory environment creates suitable conditions for cancer progression [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several systemic inflammatory markers that are easily obtained from routine blood tests, such as leukocyte, neutrophil and thrombocyte counts, have been proposed as potentially additional predictive and prognostic markers that can be used in various malignancies. In recent years, several reports established the prognostic and the predictive role of inflammatory indices, such as the neutrophil-to-lymphocyte ratio (23)(24)(25)(26)(27)(28), platelet-to-lymphocyte ratio (28,29) and the systemic immune-inflammation index (SII) (24,28,30) in testicular GCTs. All these data emphasized the important role of the immune response in GCTs (29).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several reports established the prognostic and the predictive role of inflammatory indices, such as the neutrophil-to-lymphocyte ratio (23)(24)(25)(26)(27)(28), platelet-to-lymphocyte ratio (28,29) and the systemic immune-inflammation index (SII) (24,28,30) in testicular GCTs. All these data emphasized the important role of the immune response in GCTs (29). Therefore, there is an evident need to address the influence of the immunological response on the development of GCTs, as well as on the outcome of GCT patients.…”
Section: Introductionmentioning
confidence: 99%